Knowledge of Usury, Perceived Ease of Use, Perceived Usefulness And Religiosity of The Voting Community BPR In Bukittinggi City - Nirwan Saputra; Asyari Asyari (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2024)
This study aims to find out how much influence knowledge about usury, perceived ease of use, perceived usefulness and religiosity of urban people choose BPRS in Bukittinggi City. This form of research is quantitative correlational. The population in this study is BPRS customers in Bukittinggi City with a population of 26,695 customers. In this study, a sample of 162 respondent customers. Furthermore, the determination of sampling is carried out by purposive sampling method. The criteria used in this study are the Muslim community of Bukittinggi City and become BPRS customers in Bukittinggi City. The analysis of this study used WarpPLS 5.0. The results showed that the variable Knowledge About Riba had a significant positive effect on Choosing BPRS with a significant value of 0.01 < 0.05. The variable Perceived Ease Of Use has a significant positive effect on Choosing BPRS with a significant value of 0.01 < 0.05. Perceived of Usefulness has a positive insignificant effect on Choosing BPRS with a significant value of 0.10 which means >0.05. and Religiosity has a positive and significant effect on Choosing BPRS with a significant value of 0.01 < 0.05. The results showed that Knowledge of Riba contributed to choosing BPRS by 0.89 (89%). Perceived Ease Of Use has a contribution to Choosing BPRS of 0.79 (79%). Perceived of Usefulness has a contribution value of 0.02 (2%). Religiosity has a contribution to choosing BPRS of 0.70 (70%).